1992
DOI: 10.1007/bf01291696
|View full text |Cite
|
Sign up to set email alerts
|

The decay modes of proton drip-line nuclei with A between 42 and 47

Abstract: If we analyse the semantic field of the term “anthropology” we find that the idea covers a very wide range. At the same time however, expressed opinion follows three basic ways. First of all through definitions or lists of characteristics. Or else through the choice of methods used to analyse the human fact. Finally there are the moments where a researcher admits that he can define only the contours of a concept whose core he still ignores. We can say that there exists an “anthropology” in an ethnographic sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 25 publications
4
19
0
Order By: Relevance
“…In most cases agreement was found, but in some instances we had to adjust masses. These are discussed in the following: Borrel et al (1992) with the reported observation of this isotope by Rykaczewski et al (1995). Evidence for 103 Sb was also reported by Smith et al (2006), who find a significant β-branch.…”
Section: New Massesmentioning
confidence: 69%
“…In most cases agreement was found, but in some instances we had to adjust masses. These are discussed in the following: Borrel et al (1992) with the reported observation of this isotope by Rykaczewski et al (1995). Evidence for 103 Sb was also reported by Smith et al (2006), who find a significant β-branch.…”
Section: New Massesmentioning
confidence: 69%
“…As mentioned in the introduction, after the observation of this decay mode for 22 [7], and 43 Cr [8], the identification of a β-delayed twoproton branch for 23 Si closes the list of known β2p emitters for T z = −5/2 nuclei: All nuclei of this series which have been studied experimentally, from the lightest one ( 23 Si) to the heaviest one ( 43 Cr), exhibit this decay mode. Theoretically this mode is expected to exist for all T z = −5/2 nuclei which are bound or sufficiently bound by the Coulomb barrier to decay by β decay.…”
Section: β-Delayed Two-proton Radioactivity Of 23 Simentioning
confidence: 91%
“…However, for some nuclei at the drip line, even more exotic decay branches are possible. After the first observation of β-delayed two-proton emission for 22 Al [2], 6 more β2p emitters have been found: 26 P [3], 35 Ca [4], 31 Ar [5], 27 S [6], 39 Ti [7], and 43 Cr [8]. For 31 Ar, a β-delayed three-proton emission has been reported [9a] D. Bazin et al.…”
Section: Introductionmentioning
confidence: 96%
“…For 39 Ti, the half-life and the main decay branches, including the β2p decay, have been observed previously [17,18]. Some information, like rough lifetime estimates and a few delayed proton lines, is also available for 43 Cr, 46 Mn and 46,47 Fe [19]. For the most exotic isotopes, 42 Cr, 45 Fe and 49 Ni, only their existence was reported [1].…”
Section: Introductionmentioning
confidence: 97%